European Political Science versus the Pandemic: Patterns of Professional Adaptation. (February 2023) - Capano, Giliberto; Verzichelli, Luca; Vicentini, Giulia
The emergence of the COVID-19 outbreak can be considered a potential driver of changes not only in academic disciplines but also, as most observers underline, in the teaching mission of higher education. This raises the main question of this article, that is, exactly whether and how an external shock such as COVID-19 can impact the comprehensive profile of academic disciplines. By focusing on European political science, the article assesses the differences among scholars in this community in terms of potential long-term reactions. The study, based on the outcomes of an original survey conducted among 1400 European professional political scientists (EPSs) at the end of 2020, aims at detecting the "predisposition to adaptation" of the community, by examining the attitudes revealed by EPSs during the early phase of pandemic. In this regard, we focus on the explanations of different aspects of 'professional adaptation', discussing three dimensions that seem to be present in our sample, although with very different weights: passive, proactive and innovative adaptation.